Comparative study of emission of pollutant gases in vehicle M1, using fuel of the Andean Community - Antamba Guasgua, Jaime Fernando; Reyes Campaña, Guillermo Gorky; Granja Paredes, Miguel Estuardo (Enfoque UTE, 2016)
The environmental pollution is a problematics that concerns all countries about the world as result of this pollution there take place the phenomena of climate change, greenhouse effect, acid rain, and diseases in people. To delimit the issues, there were selected the countries that integrate the Andean Community, the project goal is compare by means of static and dynamic tests the values of emission of pollutant gases, with the fuel that is distributed in each of the selected countries. The process of measuring and testing of static tests were developed under NTE INEN 2203:1999 standard, considering the idle condition (820 rpm) and high engine speed (2500 RPM), in both these cases, an constant engine oil temperature of 94 ° C and dynamic tests carried out according to ASM 25/25 and ASM 50/15 cycles, the results that have been achieved with the different fuels in a vehicle Chevrolet Sail, the best-selling in the country. Based on tests developed, the evaluated vehicle will be able to circulate without any disadvantage with any of the fuels of the Andean Community according NTE INEN 2204:2002 standard. Accordingly, the fuel with the lowest levels of emissions of gaseous pollutants is the distributed one in Peru.